Endolymphatic sac tumor: a case report - (:unkn) unknown (My University, 2001)
Papillary tumors of the temporal bone are aggressive neoplasms which may occur sporadically or as a part of von Hippel-Lindau disease. The term 'endolymphatic sac tumor' identifies the origin of these rare tumors. The clinical manifestations are sensorineural hearing loss, facial paralysis, cerebellar disorders and vertigo. The tumor is locally invasive, destructive and hypervascular exhibiting consistent imaging and histopathologic features. The treatment of choice is the total removal of the lesion although complete excision of the advanced lesion is nearly impossible due to the anatomic complexity of the endolymphatic sac and distinct patterns of extension. We present a 50-year-old male patient with endolymphatic sac tumor with left sided sensorineural hearing loss and review the literature.
Keywords: Humans; Middle Aged; Tomography, X-Ray Computed; Male; Magnetic Resonance Imaging; Severity of Illness Index; Temporal Bone; Endolymphatic Sac; Audiometry, Pure-Tone; Skull Neoplasms; Embolization, Therapeutic; Bone Conduction; Carcinoma, Papillary; Cerebral Angiography; Facial Paralysis; Hearing Loss, Sensorineural